Genome-wide Identification and Expression of ARF Gene Family during Adventitious Root Development in Hot Pepper (Capsicum annuum) - Huanxin ZHANG; Ning CAO; Chunjuan DONG; Qingmao SHANG (Horticultural Plant Journal, 2017)
Auxin response factors (ARFs) are transcription factors that activate or repress the expression of primary/early auxin response genes by binding to auxin-responsive elements (AuxREs) in their promoter regions. The ARFs play important roles in diverse developmental processes. To explore the ARF gene family in hot pepper (Capsicum annuum L.), we performed a genome-wide identification and expression analysis. In this study, 19 pepper ARF genes (CaARFs) clustered into three phylogenetic groups (I, II, and III) were comprehensively analyzed. Conserved domain analysis showed that all CaARFs contained a B3 DNA-binding domain and a middle domain, but two members lacked the carboxy-terminal dimerization (CTD) domain. The number of introns in CaARF genes ranged from 1 to 13 and the gene structure was similar among genes in the same phylogenetic group. Additionally, prediction of CaARFs promoter elements and putative targets for microRNAs suggested that the regulation of CaARFs may occur at both transcriptional and posttranscriptional levels. Most CaARFs were expressed in more than one tested tissue, and most CaARFs were identified as being responsive to exogenous auxin. Moreover, time-course transcription profiles of CaARFs revealed their roles in adventitious rooting of hypocotyl cuttings from pepper seedlings. Therefore, our results will provide a foundation for better understanding the regulatory mechanisms and molecular functions of CaARFs in hot pepper.